PELAKSANAAN PROGRAM SUNSET POLICY DALAM PENYAJIAN LAPORAN KEUANGAN PERUSAHAAN - Nurias, Neneng (EL MUHASABA: Jurnal Akuntansi (e-Journal), 2014)
Research by title sunset policy implementation in the company’s financial statement presentation. One of the government’s efforts to improve our economy is relying on tax revenue, associated with these two new tax policies applied are better known as the Sunset Policy. Sunset Policy is a policy of tax facilities in the form of administrative sanction taxation of interest on taxes not paid or less regulated in pasal 37A UU KUP (Undang-Undang Nomor 28 Tahun 2007). There are two types of sunset policy under the terms of which are: Sunset Policy For New Taxpayer and Sunset Policy For Taxpayer Older. So this is a problem in research whether there is influence sunset policy program for the company’s financial statement presentation. Data analysis technique used is qualitative analysis by comparing the tax before sunset policy and after sunset policy. The data presented in the form of figures, calculations and descriptive explanation that describes what is in the company, the more qualitative analysis of the problem. Based on these results it can be concluded that the presence of a sunset policy program undertaken by the government, many taxpayers who voluntarily report the amount of income tax to be paid correctly but many taxpayers who are concerned over the financial statements that have been reported to the Tax office, so that they consciously includes in the report that have been made so that they are free from administrative penalties and fines.